THE DEPARTMENT OF EDUCATION DURING THE PERONISMO: IDEOLOGY, CENTRALIZATION, BUROCRAZY AND ADMINISTRATIVE RATIONALIZATION (1949-1955) - Cammarota, Adrián (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The article analyses the Ministry of Education genesis in the year of 1949 during the designees of the first Peronista government, during these years to demonstrate the need to centralize the system of education and the politics of administrative rationalization and imposition of the official ideology in a context of democratization of the social rights.